Impact of global financial crisis on firm performance in UK: Moderating role of ESG, corporate governance and firm size - Nisar Ahmad; Asma Mobarek; Moodhi Raid (Cogent Business & Management, 2023)
AbstractThis paper investigates the impact of global financial crisis (GFC; 2007–10) on financial and non-financial performance of FTSE350 UK firms. This study tests the relationships among GFC, firm financial performance and environmental, social and governance (ESG; for non-financial performance) and estimates the moderating role of ESG, corporate governance (CG) and firm size in these relationships. Panel data from 2002 to 2018 across 351 UK firms are used. For estimation, random effect model is found suitable to investigate the relationship between financial crisis and firm performance (financial performance as well as ESG performance). The results explain that financial as well as ESG performance of the firm declined during the financial crisis period. Firm size is a moderator in the relationship of financial crisis and ESG performance of the firm. Further findings of the study explain that ESG, firm size and CG are the moderators in the relationship of GFC and firm financial performance. The results of the study are data based and can be used for policy implications. Firms can employ ESG, CG and firm size as strategy tools to enhance their performance especially during the financial crisis periods.